Etch Pit Density Reduction in POCl3 and Atmospheric Pressure Chemical Vapor Deposition‐Gettered mc‐Si. Issue 17 (7th August 2019) - Fleck, Martin; Zuschlag, Annika; Hahn, Giso
Abstract : Herein, the effects of gettering, temperature, dopant concentration, and metal contamination on the etch pit density (EPD) of an mc‐Si material are studied. It is demonstrated that there is a reduction of EPD after gettering that is independent for varying etchants, thereby confirming the physical nature of this effect. The EPD analysis of wafers that are gettered on one wafer side, results in different EPD values for the two wafer sides. This finding constrains the possibilities for mechanisms of EPD reduction. The combined evidence of the experiments presented here supports the hypothesis that EPD reduction happens because the defect etching process for impurity‐lean dislocations is different from dislocations decorated with impurities. Abstract : The measured etch pit density in mc‐Si material is shown to be reduced by P‐gettering. Various pieces of evidence are presented, suggesting that defect etching does not reveal impurity‐lean dislocations.